KESADARAN MAHASISWA DALAM BERETIKA DI ZAMAN ERA DIGITAL - Muldiah, Siti (STAI Darul Qalam Tangerang, 2023)
In the era of rapid development of technology and science, including the development of social ethics as well as media and technology that is so fast, especially in the digital era. In the digital era, the distance between one region and another is relatively closer, which makes it very easy for users to interact with anyone. Therefore, it is very important for students to be ethical in this day and age. Ethics is a norm or boundaries in life, in which there are rules that will require students to behave, interact and communicate well. This study used qualitative research methods. From the research results obtained information that students' awareness of ethics is very important. Especially in the norm of courtesy, it is very necessary in the era of the digital era. Awareness of ethical students can be explored through a good understanding of grammar, early education about manners, learning to understand and limiting curiosity about the privacy of others